Roles of organic anion transporting polypeptides in hepatocellular carcinoma - Chen, Hubert (Frontiers in Genetics, 2025)
IntroductionHepatocellular carcinoma (HCC) is the most common primary liver malignancy, predominantly occurring in patients with underlying chronic liver disease, including cirrhosis. Organic anion transporter polypeptides (OATPs), encoded by SLCO genes, are one of the most important SLC subfamilies involved in the cellular uptake of drugs and endobiotic. OATP1B1 (SLCO1B1 gene), OATP1B3 (SLCO1B3 gene), and OATP2B1 (SLCO2B1 gene) are hepatic uptake transporters highly expressed in the liver. We aimed to systematically analyze expression levels of SLCO1B1, SLCO1B3, and SLCO2B1 and to investigate their prognostic role in predicting HCC clinical outcomes using open-source databases.MethodsA comparison of HCC and matched normal tissue gene and protein expression was performed using the TCGA and CPTAC datasets through UALCAN. The correlation between SLCO gene and protein expression with patient survival was evaluated using OncoLnc, KM-Plotter, and OSppc. SLCO genetic alterations in HCC were explored using cBioPortal. A protein-protein interaction map for SLCO1B1, SLCO1B3, and SLCO2B1 was also constructed using STRING.ResultsGene and protein expression levels of SLCO1B1, SLCO1B3, and SLCO2B1 were significantly downregulated in HCC patients compared to normal counterparts. Clinically, the low gene expression of SLCO1B1, SLCO1B3, and SLCO2B1 was correlated with shorter survival rate in HCC patients. Kaplan-Meier analysis further confirmed that low protein levels of these transporters predicted poor prognosis for HCC patients. Analysis of the TCGA Liver Hepatocellular Carcinoma dataset (TCGA’s Pan-Cancer Atlas) revealed a low mutation and amplification frequency in HCC for SLCO1B1 (0.57% vs. 0.29%), SLCO1B3 (0.86% vs. 0.29%), and SLCO2B1 (0.57% vs. 0.86%), respectively. Network analysis highlighted non-random interconnectivity among SLCO1B1, SLCO1B3, and SLCO2B1.ConclusionSLCO1B1, SLCO1B3, and SLCO2B1 are highly expressed in the liver and play key roles in many liver diseases. In HCC patients, the downregulation of SLCO1B1, SLCO1B3, and SLCO2B1 expression has been observed. SLCO genes such as SLCO1B1, SLCO1B3, and SLCO2B1 expression levels may also serve as prognostic predictive markers in HCC patients.